Toward a platform for the treatment of burns: An assessment of nanoemulsions vs. nanostructured lipid carriers loaded with curcumin - Araújo, Gabriela de Moraes Soares (2023)
Curcumin is a highly promising substance for treating burns, owing to its anti-inflammatory, antioxidant, antimicrobial, and wound-healing properties. However, its therapeutic use is restricted due to its hydrophobic nature and low bioavailability. This study was conducted to address these limitations; it developed and tested two types of lipid nanocarriers, namely nanoemulsions (NE-CUR) and nanostructured lipid carriers (NLC-CUR) loaded with curcumin, and aimed to identify the most suitable nanocarrier for skin burn treatment. The study evaluated various parameters, including physicochemical characteristics, stability, encapsulation efficiency, release, skin permeation, retention, cell viability, and antimicrobial activity. The results showed that both nanocarriers showed adequate size (~200 nm), polydispersity index (~0.25), and zeta potential (~>20 mV). They also showed good encapsulation efficiency (>90%) and remained stable for 120 days at different temperatures. In the release test, NE-CUR and NCL-CUR released 57.14% and 51.64% of curcumin, respectively, in 72 h. NE-CUR demonstrated better cutaneous permeation/retention in intact or scalded skin epidermis and dermis than NLC-CUR. The cell viability test showed no toxicity after treatment with NE-CUR and NLC-CUR up to 125 g/mL. Regarding microbial activity assays, free curcumin has activity against P. aeruginosa, reducing bacterial growth by 75% in 3 h. NE-CUR inhibited bacterial growth by 65% after 24 h, and the association with gentamicin had favorable results, while NLC-CUR showed a lower inhibition. The results demonstrated that NE-CUR is probably the most promising nanocarrier for treating burns.